Cloud Platform Task Scheduling Strategy for Power Dispatching Automation System Based on Artificial Intelligence Algorithm. (June 2020) - Li, Shiming; Li, Bo; Wang, Ke; Guo, Wenxin; Liu, Yang; Zhao, Ruifeng; Zeng, Jianyong; Li, Haobin; Lin, Yueting
Abstract: As the command and control center of the whole power grid operation, the power dispatching system has huge and complex data information, which makes the traditional power grid dispatching information platform difficult to meet the needs of power grid operation monitoring in information integration, analysis, calculation and storage. Therefore, cloud platform is introduced into the construction of power dispatching automation system. This paper takes the power dispatching automation cloud platform as the research object, studies its architecture, and proposes a cloud platform task scheduling model based on improved particle swarm optimization, aiming to improve the efficiency of cloud computing resource allocation, improve the quality of cloud services, and solve the task scheduling problem of the power dispatching automation system.